Copper-mediated chemodynamic therapy with ultra-low copper consumption by doping cupric ion on cross-linked (R)-(+)-lipoic acid nanoparticles. (23rd March 2023) - Cui, Rong; Li, Bing; Liao, Chunyan; Zhang, Shiyong
Abstract: Cu-mediated chemodynamic therapy (CDT) has attracted prominent attention owing to its advantages of pH independence and high efficiency comparing to Fe-mediated CDT, while the application of Cu-based CDT agents was impeded due to the high copper consumption caused by the metabolism loss of copper and the resultant potential toxicity. Herein, we developed a new copper-mediated CDT agent with extremely low Cu usage by anchoring copper on cross-linked lipoic acid nanoparticles (Cu@cLAs). After endocytosis into tumor cells, the Cu@cLAs were dissociated into LA and dihydrolipoic acid (DHLA) (reduced form of LA) and released Cu 2+ and Cu + (oxidized form of Cu 2+ ), the two redox couples recycled each other in cells to achieve the efficient killing of cancer cells by delaying metabolic loss and increasing the ROS level of tumor cells. The self-recycling was confirmed in cells by the sustained high Cu/DHLA content and persistent ROS generation process. The antitumor study based on the MCF-7/R nude mice gave the Cu@cLAs a tumor inhibitory rate up to 77.9% at the copper of 0.05 mg kg −1, the first dosage reported so far lower than that of normal serum copper (0.83 ± 0.21 mg kg −1 ). This work provides not only a new promising clinical strategy for the copper excessive use in copper-mediated CDT, but also gives a clue for other metal mediated disease therapies with the high metal consumption. Graphical Abstract: